2009
DOI: 10.1002/nbm.1388
|View full text |Cite
|
Sign up to set email alerts
|

Repeatability of a dual gradient‐recalled echo MRI method for monitoring post‐isometric contraction blood volume and oxygenation changes

Abstract: The purpose of this study was to assess the repeatability of a dual gradient-recalled echo (GRE) muscle functional MRI technique. On two days, subjects (n=8) performed 10 s isometric dorsiflexion contractions under conditions of: 1) maximal voluntary contraction (MVC), 2) 50% MVC (50%MVC) or 3) 50% MVC with concurrent proximal arterial cuff occlusion (50%MVCcuff). Functional MRI data were acquired using single-slice dual GRE (TR/TE=1000/6, 46 ms) EPI for 20 seconds before, during, and for 180 seconds after eac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 41 publications
1
15
1
Order By: Relevance
“…In young muscle, Sanchez et al, previously showed good reliability, based on ICC, for peak AC BOLD responses under similar conditions (TR/TE=1000/46ms, 10s MVC), but not for TTP (33). The reliability of peak and TTP BOLD response in older adults was excellent for AC and SOL.…”
Section: Discussionmentioning
confidence: 96%
“…In young muscle, Sanchez et al, previously showed good reliability, based on ICC, for peak AC BOLD responses under similar conditions (TR/TE=1000/46ms, 10s MVC), but not for TTP (33). The reliability of peak and TTP BOLD response in older adults was excellent for AC and SOL.…”
Section: Discussionmentioning
confidence: 96%
“…At each TE, the mean functional image SI for the ROI was calculated as a function of time and divided by the corresponding mean precontraction SI value. An average SI time course from each TE was obtained by averaging the SI time course from the four trials from each intensity (SI 6 and SI46), as previously described (56). The averaged SI time course was fitted to a polynomial function, and inflections in the derivative of this polynomial were used to identify the minimum and maximum postcontraction SI values.…”
Section: Subjectsmentioning
confidence: 99%
“…Building on these studies, we have used a dual-gradientrecalled echo (GRE) MRI sequence to study blood volume (V B ) and oxyhemoglobin saturation (%HbO 2 ) changes in small vessels of the muscle tissue bed following isometric contractions noninvasively, and with high temporal resolution (1 s) (13) and sufficient repeatability (56). This method consists of measuring the MRI signal intensity (SI) at two echo times (TE): 6 and 46 ms.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The average SI of the three regions-of-interest was measured as a function of time in the functional images and the weighted average was calculated (Figure 1D). Each postcontractile transient was fitted to a ninth order polynomial using MATLAB’s polyfit function, similar to the procedure described in Reference (23). The peak signal was obtained from the line of best fit and the time-to-peak signal was determined by identifying the inflection in the derivative of the line of best fit.…”
Section: Methodsmentioning
confidence: 99%